O potencial de LA para o moodle do curso de licenciatura em computação: um estudo de caso - Moreira, Salviano Gonçalves (2018)
This work presents a study of case of the potential of LA (Learning Analytics), for the atmosphere Moodle in the Course of Degree in Computation, modality the distance, specifically in the disciplines of Introduction to the Programming and Matemática Element, motivated for the high retention index and disapproval of those disciplines. It was sought the observation and consequent proof / reply of the developed learning. Trying to determine the reasons of the learning difficulty in the process teaching-learning applied and the positive contribution that the Analytical of the Learning could offer to revert such picture and to favor the acting earnings in the teaching-learning. The contribution of the resources of LA was discussed made available for the platform Moodle and tools that can be joined the east seeking the improvement of the process teaching learning.